Nitrogen-doped carbon-supported transition metal monatomic material as well as preparation method and application thereof
By using nitrogen-doped carbon-loaded transition metal single-atom material as an electrocatalyst, the problems of low selectivity and high cost of CO2 reduction in the prior art are solved, and efficient and low-cost CO2 reduction conversion is achieved, and the material preparation is simple and suitable for large-scale production.
Patent Information
- Application Number
- CN202311421265.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing electrocatalytic carbon dioxide reduction technology has problems such as low product selectivity, high catalyst electrode cost, and high electrolytic energy consumption, making it difficult to achieve efficient and low-cost CO2 reduction conversion.
The Fe-CN and Ni-CN single atomic materials were prepared by grinding and pyrolyzing a mixture containing a transition metal precursor, a nitrogen source and a carbon source as an electrocatalyst, and Fe-CN single atomic materials were prepared for electrochemical CO2 reduction reaction.
This material can efficiently catalyze CO2 reduction to CO in CO2 saturated KHCO3 electrolyte, with selectivity higher than 90%. The preparation method is simple, suitable for large-scale production, and exhibit excellent catalytic activity, selectivity and stability.
Smart Images

Figure CN119900041A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of inorganic catalyst materials, and in particular relates to a nitrogen-doped carbon-supported transition metal single atom material and a preparation method and application thereof. Background Art
[0002] The massive consumption of fossil fuels has led to a sharp increase in the concentration of carbon dioxide in the atmosphere, causing severe environmental and energy crises. It is urgent to develop green renewable energy conversion technologies to reduce carbon emissions. Among them, the electrocatalytic reduction of carbon dioxide into high-value chemicals such as carbon monoxide, formic acid, and ethylene is an effective strategy to reduce the concentration of CO2 in the atmosphere. At present, the large-scale application of electrochemical CO2 reduction (CO2RR) still has problems such as low product selectivity, high catalyst electrode cost, and high electrolysis energy consumption. Therefore, the development of low-cost, highly active, highly selective, and well-stable catalyst materials is the key to achieving efficient electrochemical CO2 reduction conversion.
[0003] Metal single-atom anchored doped carbon materials have unique electronic and geometric structures and exhibit excellent stability and catalytic activity in the catalytic process. The current synthesis of carbon-based single-atom catalysts has complex preparation processes and is difficult to prepare on a large scale. The development of efficient and rapid methods for preparing single-atom catalysts to synthesize single-atom catalysts with excellent performance for efficient electrocatalytic CO2 reduction has attracted much attention. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a nitrogen-doped carbon-supported transition metal single atom material, a preparation method and application thereof. The nitrogen-doped carbon material-supported Fe single atom and the nitrogen-doped carbon material-supported Ni single atom material in the material serve as electrocatalysts for the electrochemical carbon dioxide reduction reaction, have good catalytic effects, high catalytic efficiency and good stability, and the preparation method of the material is simple and can be mass-produced.
[0005] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:
[0006] On the one hand, the present application provides a method for preparing a nitrogen-doped carbon-supported transition metal single atom material, comprising the following steps:
[0007] (1) grinding a mixture containing a transition metal precursor, a nitrogen source, and a carbon source to obtain an initial mixture;
[0008] (2) placing the initial mixture in an inert gas atmosphere for pyrolysis to obtain the nitrogen-doped carbon-supported transition metal single atom material;
[0009] The molar ratio of the transition metal precursor to the nitrogen source in step (1) is 1:150-90000, wherein the molar number of the transition metal precursor is calculated based on the atomic molar number of the transition metal therein, and the molar number of the nitrogen source is calculated based on the molar number of the substance itself.
[0010] Optionally, the molar ratio of the transition metal precursor to the nitrogen source in step (1) is independently selected from any value of 1:150, 1:450, 1:1000, 1:5000, 1:30000, 1:90000 or any range between two values.
[0011] Optionally, the transition metal precursor in step (1) includes at least one of nitrates, acetates and acetylacetonates of transition metals.
[0012] Optionally, the transition metal includes at least one of Cr, Mn, Fe, Co, Ni, Cu, and Zn.
[0013] Optionally, the nitrogen source in step (1) includes at least one of urea, dicyandiamide, melamine and peptone.
[0014] Optionally, the carbon source in step (1) includes at least one of glucose, chitosan, starch, sucrose and citric acid.
[0015] Optionally, the mass ratio of the carbon source to the nitrogen source in step (1) is 1:1 to 20.
[0016] Optionally, the mass ratio of the carbon source to the nitrogen source in step (1) is independently selected from any value of 1:1, 1:1.5, 1:5, 1:6, 1:10, 1:15, 1:20 or any range value therebetween.
[0017] Optionally, the grinding time in step (1) is 0.5 to 4 hours.
[0018] Optionally, the grinding time in step (1) is independently selected from any value among 0.5h, 1h, 2h, 3h, 4h, or any range between two values.
[0019] Optionally, ethanol is added during the grinding in step (1), and the ratio of the ethanol to the mixture is 1.5-2.5 mL:10 g.
[0020] Optionally, the grinding in step (1) is performed in a mortar or a ball mill.
[0021] Optionally, the rotation speed of the ball mill is 450-550 r / min.
[0022] Optionally, the rotation speed of the ball mill is independently selected from any value among 450r / min, 480r / min, 500r / min, 520r / min, 550r / min, or any range value therebetween.
[0023] Optionally, the inert gas in step (2) includes nitrogen and / or argon.
[0024] Optionally, the gas flow rate of the inert gas is 20 to 50 mL / min.
[0025] Optionally, the gas flow rate of the inert gas is independently selected from any value among 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, or any range value therebetween.
[0026] Optionally, the pyrolysis in step (2) includes pyrolysis I and pyrolysis II.
[0027] Optionally, the temperature of the pyrolysis I is 550-650°C;
[0028] The time of the pyrolysis I is 1 to 3 hours.
[0029] Optionally, the temperature of the pyrolysis I is independently selected from any value of 550°C, 580°C, 600°C, 620°C, 650°C, or any range therebetween.
[0030] Optionally, the time of the pyrolysis I is independently selected from any value among 1 h, 2 h, 3 h, or any range between the two.
[0031] Optionally, the temperature of the pyrolysis II is 800-1100°C;
[0032] The time of the pyrolysis II is 0.5 to 3 hours.
[0033] Optionally, the temperature of the pyrolysis II is independently selected from any value among 800°C, 900°C, 1000°C, 1100°C or any range therebetween.
[0034] Optionally, the time of the thermal decomposition II is independently selected from any value among 0.5h, 1h, 2h, 3h, or any range between the two.
[0035] Optionally, the heating rate from pyrolysis I to pyrolysis II is 2 to 5°C / min.
[0036] Optionally, the heating rate from pyrolysis I to pyrolysis II is independently selected from any value of 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any range therebetween.
[0037] In a second aspect, the present application provides a nitrogen-doped carbon-supported transition metal single atom material prepared by the above preparation method.
[0038] In a third aspect, the present application provides the application of the above-mentioned nitrogen-doped carbon-supported transition metal single atom material as a catalyst material.
[0039] In a fourth aspect, the present application provides the application of the above-mentioned nitrogen-doped carbon-supported transition metal single atom material in electrocatalytic carbon dioxide reduction.
[0040] Compared with the prior art, this application has the following beneficial effects:
[0041] (1) The nitrogen-doped carbon-supported transition metal single atom materials provided in the present application, taking Fe-CN and Ni-CN single atom materials as examples, can efficiently catalyze the reduction of CO2 to CO in a CO2-saturated KHCO3 electrolyte, with a selectivity of more than 90%.
[0042] (2) The preparation method of nitrogen-doped carbon-supported transition metal single atom material provided in this application is universal and easy to scale up for production, and can be used to synthesize other similar single atom materials.
[0043] (3) The nitrogen-doped carbon-supported transition metal single atom material prepared in this application is applied as an electrocatalyst in CO2RR, which can exhibit excellent catalytic activity, selectivity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 X-ray powder diffraction patterns of Ni-CN and Fe-CN in this application;
[0046] Figure 2 Electron microscope images of Fe-CN of the present application (Note: (a) represents a scanning electron microscope image of Fe-CN; (b) represents a transmission electron microscope image of Fe-CN; (c) represents a high-magnification transmission electron microscope image of Fe-CN; (d) represents a spherical aberration electron microscope image of Fe-CN);
[0047] Figure 3 Electron microscope images of Ni-CN of the present application (Note: (a) represents a scanning electron microscope image of Ni-CN; (b) represents a transmission electron microscope image of Ni-CN; (c) represents a high-magnification transmission electron microscope image of Ni-CN; (d) represents a spherical aberration electron microscope image of Ni-CN);
[0048] Figure 4 The Faradaic efficiency curve of the Fe-CN / CC catalyst electrode used for electrocatalytic carbon dioxide reduction to generate CO at different potentials (relative to the reversible hydrogen electrode) in this application;
[0049] Figure 5 This is a Faradaic efficiency curve of the Ni-CN / CC catalyst electrode used for electrocatalytic carbon dioxide reduction to generate CO at different potentials (relative to the reversible hydrogen electrode) in this application. DETAILED DESCRIPTION
[0050] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0051] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0052] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0053] The instruments used in the following examples are: field emission transmission electron microscope (Tecnai F20), electrochemical workstation (CHI760, Shanghai Chenhua), spherical aberration electron microscope (JEM-ARF200F).
[0054] Example 1
[0055] Preparation of single-atom material Fe-CN samples:
[0056] (1) Ferrous acetylacetonate (0.1 mmol), melamine (5 g), and glucose (0.3 g) were weighed and ground in a mortar for 1 h (1.5 mL of ethanol was added during grinding);
[0057] (2) The obtained initial mixture was placed in a tubular furnace under an argon atmosphere with an inert gas flow rate controlled at 30 mL / min. After a two-step pyrolysis method (the temperature was raised to 600°C at a rate of 2°C / min at room temperature, then kept at 600°C for 2 h, then raised to 900°C at a rate of 2°C / min and kept for 1 h, and then naturally cooled), a porous carbon-supported iron single atom material was obtained.
[0058] Example 2
[0059] Preparation of single-atom material Ni-CN samples:
[0060] (1) Weigh nickel acetate monohydrate (0.1 mmol), melamine (5 g) and glucose (0.3 g) and grind them in a mortar for 1 h (add 1.5 mL of ethanol during grinding);
[0061] (2) The obtained initial mixture was placed in a tubular furnace under an argon atmosphere with an inert gas flow rate controlled at 30 mL / min. After a two-step pyrolysis method (the temperature was raised to 600°C at a rate of 2°C / min at room temperature, then kept at 600°C for 2 h, then raised to 900°C at a rate of 2°C / min and kept for 1 h, and then naturally cooled), a porous carbon-supported nickel single atom material was obtained.
[0062] Example 3
[0063] Characterization of single-atom material samples:
[0064] The phase and morphology of Fe-CN samples were tested by X-ray powder diffractometer, scanning electron microscope and transmission electron microscope. Figure 1 As shown, X-ray powder diffraction showed no obvious Fe-related nanoparticles ( Figure 1 ), scanning electron microscopy showed that the Fe-CN sample was a graphene-like nanosheet structure ( Figure 2 (a) in the figure). The morphology of the Fe-CN sample was further tested using a transmission electron microscope. The test results showed that the Fe-CN sample was a porous nanosheet structure ( Figure 2 (b) and (c) in the figure). The existence form of metal atoms was detected using a spherical aberration electron microscope. The test results showed that Fe in the sample existed in the form of single atoms ( Figure 2 (d) in the figure.
[0065] X-ray powder diffractometer, scanning electron microscope and transmission electron microscope were used to detect the phase and morphology of Ni-CN samples. Figure 1 As shown, X-ray powder diffraction showed no obvious Ni-related nanoparticles ( Figure 1 ), scanning electron microscopy shows that the Ni-CN sample is a graphene-like nanosheet structure ( Figure 3 (a) in the figure). The morphology of the Ni-CN sample was further tested using a transmission electron microscope. The test results showed that the Ni-CN sample was a porous nanosheet structure ( Figure 3 (b) and (c) in the figure). The existence form of metal atoms was detected by spherical aberration electron microscopy. The test results showed that Ni in the sample existed in the form of single atoms ( Figure 3 (d) in the figure.
[0066] Example 4
[0067] Preparation of Fe-CN coated on carbon paper (Fe-CN / CC) electrode:
[0068] The Fe-CN single atom material prepared in Example 1 was used as a carbon dioxide reduction catalyst and loaded on carbon paper. The sample loading on the electrode surface was 0.5 mg / cm 2 The electrode prepared is Fe-CN / CC.
[0069] Taking Fe-CN as an example, the specific steps for preparing the electrode Fe-CN / CC are as follows: 3 mg of the synthesized sample is dispersed in 600 μL of a mixed solution of water, ethanol, isopropanol and perfluorosulfonic acid (nafion) (volume ratio is water: ethanol: isopropanol: nafion = 9:6:3:2) and ultrasonically dispersed to form a suspension, and the suspension is dropped on a carbon cloth (the area of the carbon paper is 1×1.5 cm 2 ) to make the sample loading on the carbon paper electrode 0.5 mg / cm 2 After natural drying, an electrode sheet for catalyzing carbon dioxide reduction is obtained, which is denoted as Fe-CN / CC.
[0070] Example 5
[0071] Electrochemical test of electrode Fe-CN / CC:
[0072] The catalytic activity and selectivity of the electrode Fe-CN / CC in Example 4 were tested. The carbon dioxide reduction reaction (abbreviated as CO2RR) was tested in 0.5M KHCO3 saturated with CO2, and the distribution of the catalytic carbon dioxide reduction products at different potentials was tested.
[0073] The results show that the electrode Fe-CN / CC exhibits good CO2RR catalytic performance and can achieve a Faradaic efficiency of more than 90% for CO generation in a wide potential window ( Figure 4 ), demonstrating the excellent selectivity of the Fe-CN / CC electrode for catalytic CO2 reduction.
[0074] Example 6
[0075] Preparation of Ni-CN coated on carbon paper (Ni-CN / CC) electrode:
[0076] The Ni-CN single atom material prepared in Example 2 was used as a carbon dioxide reduction catalyst and loaded on carbon paper. The sample loading on the electrode surface was 0.5 mg / cm 2 The electrode prepared is Ni-CN / CC.
[0077] Taking Ni-CN as an example, the specific steps for preparing the electrode Ni-CN / CC are as follows: 3 mg of the synthesized sample is dispersed in 600 μL of a mixed solution of water, ethanol, isopropanol and perfluorosulfonic acid (nafion) (volume ratio is water: ethanol: isopropanol: nafion = 9:6:3:2) and ultrasonically dispersed to form a suspension, and the suspension is dropped on a carbon cloth (the area of the carbon paper is 1×1.5 cm 2 ) to make the sample loading on the carbon paper electrode 0.5 mg / cm 2 After natural drying, an electrode sheet for catalyzing carbon dioxide reduction is obtained, which is denoted as Ni-CN / CC.
[0078] Example 7
[0079] Electrochemical test of electrode Ni-CN / CC:
[0080] The catalytic activity and selectivity of the electrode Ni-CN / CC in Example 6 were tested. The carbon dioxide reduction reaction (abbreviated as CO2RR) was tested in 0.5M KHCO3 saturated with CO2, and the distribution of the catalytic carbon dioxide reduction products at different potentials was tested.
[0081] The results show that the electrode Ni-CN / CC exhibits good CO2RR catalytic performance, and can achieve a Faradaic efficiency of more than 90% for CO generation at low potential ( Figure 5 ), demonstrating the excellent selectivity of the Ni-CN / CC electrode for catalytic carbon dioxide reduction.
[0082] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing nitrogen-doped carbon-supported transition metal single atom material, characterized in that: The steps include: (1) grinding a mixture containing a transition metal precursor, a nitrogen source, and a carbon source to obtain an initial mixture; (2) placing the initial mixture in an inert gas atmosphere for pyrolysis to obtain the nitrogen-doped carbon-supported transition metal single atom material; The molar ratio of the transition metal precursor to the nitrogen source in step (1) is 1:150-90000, wherein the molar number of the transition metal precursor is calculated based on the atomic molar number of the transition metal therein, and the molar number of the nitrogen source is calculated based on the molar number of the substance itself.
2. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The transition metal precursor in step (1) comprises at least one of nitrate, acetate and acetylacetonate of transition metal; Preferably, the transition metal includes at least one of Cr, Mn, Fe, Co, Ni, Cu, and Zn.
3. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The nitrogen source in step (1) comprises at least one of urea, dicyandiamide, melamine and peptone; Preferably, the carbon source in step (1) comprises at least one of glucose, chitosan, starch, sucrose and citric acid.
4. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The mass ratio of the carbon source to the nitrogen source in step (1) is 1:1-20.
5. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The grinding time in step (1) is 0.5 to 4 hours; Preferably, ethanol is added during the grinding in step (1), and the ratio of the ethanol to the mixture is 1.5-2.5 mL:10 g; Preferably, the grinding in step (1) is performed in a mortar or a ball mill; Preferably, the rotation speed of the ball mill is 450-550 r / min.
6. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The inert gas in step (2) includes nitrogen and / or argon; Preferably, the gas flow rate of the inert gas is 20 to 50 mL / min.
7. The method for preparing a nitrogen-doped carbon-supported transition metal single atom material according to claim 1, characterized in that: The pyrolysis in step (2) includes pyrolysis I and pyrolysis II; Preferably, the temperature of the pyrolysis I is 550-650°C; The time of the pyrolysis I is 1 to 3 hours; Preferably, the temperature of the pyrolysis II is 800-1100°C; The pyrolysis II time is 0.5 to 3 hours; Preferably, the heating rate from pyrolysis I to pyrolysis II is 2-5°C / min.
8. The nitrogen-doped carbon-supported transition metal single atom material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the nitrogen-doped carbon-supported transition metal single atom material as claimed in claim 8 as a catalyst material.
10. Use of the nitrogen-doped carbon-supported transition metal single atom material according to claim 8 in electrocatalytic carbon dioxide reduction.
Citation Information
Cited By
Monatomic carbon-based catalyst with reticular cross-linked structure as well as preparation method and application of monatomic carbon-based catalyst
CN120666391A
Monatomic / nitrogen-doped carbon sphere material as well as preparation method and application thereof
CN121651335A